2008
DOI: 10.1177/1545109708318526
|View full text |Cite
|
Sign up to set email alerts
|

General Health Status and Adherence to Antiretroviral Therapy

Abstract: General health status was the strongest predictor of HAART nonadherence, and future research is needed to assess whether this 1-question general health measure can be clinically used to influence adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
3
9
1
Order By: Relevance
“…Similar to our finding, Cardarelli and colleagues [35] reported that individuals who perceived their health as fair or poor were several times more likely to have poorer adherence to their antiretroviral medications. This implies that general health status may serve as a proxy for stress, depression and other psychosocial variables that negatively impact adherence and health [36].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our finding, Cardarelli and colleagues [35] reported that individuals who perceived their health as fair or poor were several times more likely to have poorer adherence to their antiretroviral medications. This implies that general health status may serve as a proxy for stress, depression and other psychosocial variables that negatively impact adherence and health [36].…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, whereas Cardarelli et al [46], Rao et al [57], Sayles et al [53], and Tyer-Viola et al [51] all found significant univariate associations between stigma and self-reported adherence among PLWH, these associations diminished to non-significance at the multivariate level, with other factors including mental health symptoms, depressive symptoms, and perceived general health status emerging as significant predictors. In another investigation [52], a combined stigma measure composed of four subscales (i.e., stereotypes of HIV, disclosure concerns, renegotiating social relationships, self-acceptance) was associated with adherence in univariate analyses, but adherence failed to predict any of the individual stigma subscales at the multivariate level.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 91%
“…The most frequently used measure was an original or modified version of Berger's HIV Stigma Scale [46][47][48][49][50][51], which includes four subscales of personalized stigma, disclosure concerns, negative self-image, and concern with public attitudes. In other investigations, stigma was assessed through a variety of instruments including the HIV Internalized Stigma Measure [52,53], HIV/AIDS Stigma Instrument-PLWA [54], Self-Stigma Scale [55], HIV/AIDS-related Stigma and Discrimination [56], Stigma Scale for Chronic Illness [57], and items selected from the Patient Medication Adherence Questionnaire [52].…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 99%
“…Factors that been shown to affect antiretroviral adherence include age [8][9][10], HIV risk factor [11], general health status [12], living with children [13], patients' beliefs about their need for ART and their concerns about potential adverse effects of ART [14,15], frequency and severity of symptoms [8,16,17], stressful life events [18], depression [19][20][21][22][23], mistrust of the medical system [24], HIV stigma [25], and health literacy independent of education [26]. Further, adherence can vary over the course of HIV infection [27].…”
Section: Introductionmentioning
confidence: 99%